AN ANALYSIS OF TEACHER-STUDENTS’ INTERACTION IN CROSS-CULTURAL UNDERSTANDING ONLINE TEACHING - Rika Maelasari; Ratnawati Ratnawati; Wawan Tarwana (JALL (Journal of Applied Linguistics and Literacy), 2020)
This article reports on teacher-students’ interaction in cross-cultural understanding online teaching. There are several compelling reasons for using the online teaching through the internet-based Project Work in the classroom; a structured way for teacher to begin to incorporate the internet into the language classroom, the use of projects encourage cooperative learning and stimulates interaction, gives the learners a more ‘real-world’ look and feel and provide greater motivation for the learners. This research employed a case study by means of three data collection techniques, they were observation, interview, and questionnaire. The result of this research was that online teaching helped the students in understanding the material in the CCU classroom. Moreover, the interaction between teacher and students were quite positive during the online teaching. It is suggested for further researchers to conduct a similar study with different frameworks such as online teaching strategies to give more significant contributions to the teaching and learning process.Keywords: Cross-Cultural Understanding, Interaction, Online Teaching